Інноваційна діяльність підприємства будівельного комплексу: проблеми та пропозиції щодо їхнього вирішення - Жеребйов, Я. І. (Ways to Improve Construction Efficiency, 2012)
In the article considering problems of self-organization productionly-economical sistems in the sphere of innovationly activity and proposing version their decision for leading organization Donbass construction complex.